Mycobacterium bovis BCG as immunostimulating agent prevents the severe form of chronic experimental Chagas disease - Arce-Fonseca, Minerva; Mata-Espinosa, Dulce; Aranda-Fraustro, Alberto; Rosales-Encina, José Luis; Flores-Valdez, Mario Alberto; Rodríguez-Morales, Olivia (Frontiers in Immunology, 2024)
Introduction There is currently no vaccine against Chagas disease (ChD), and the medications available confer multiple side effects. Mycobacterium bovis Bacillus Calmette–Guérin (BCG) produces balanced Th1, Th2, and Th17 modulatory immune responses and has improved efficacy in controlling chronic infections through nonspecific immunity. We aimed to improve the response to infection by inducing a stronger immune response and greater protection against the parasite by trained immunity. Methods BALB/c mice were immunized with BCG subcutaneously, and 60 days later, they were infected with Trypanosoma cruzi intraperitoneally. An evaluation of the progression of the disease from the acute to the chronic stage, analyzing various aspects such as parasitemia, survival, clinical status, and humoral and cellular immune response, as well as the appearance of visceral megas and the histopathological description of target organs, was performed. Results Vaccination reduced parasitemia by 70%, and 100% survival was achieved in the acute stage; although the presentation of clinical signs was reduced, there was no increase in the antibody titer or in the differential production of the isotypes. Conclusion Serum cytokine production indicated a proinflammatory response in infected animals, while in those who received BCG, the response was balanced by inducing Th1/Th2-type cytokines, with a better prognosis of the disease in the chronic stage.